2002
DOI: 10.1016/s0735-1097(02)02563-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vardenafil, a potent and highly selective phosphodiesterase-5 inhibitor for the treatment of erectile dysfunction, on the cardiovascular response to exercise in patients with coronary artery disease

Abstract: Vardenafil 10 mg did not impair the ability of patients with stable CAD to exercise at levels equivalent or greater than that attained during sexual intercourse (average of 2.5 to 3.3 METS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
2
3

Year Published

2004
2004
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(74 citation statements)
references
References 23 publications
2
65
2
3
Order By: Relevance
“…37 As with sildenafil, exercise testing in men with stable coronary artery disease, showed that vardenafil at 10 mg did not impair the ability of 41 patients to exercise at levels equivalent or greater than attained during sexual intercourse. 38 At baseline (1 h after taking vardenafil or placebo), systolic and diastolic blood pressure was 6 and 5 mm Hg less, respectively, with vardenafil than placebo, and heart rate was 3 beats/min higher. 38 At peak exercise, vardenafil did not alter blood pressure or heart rate, relative to placebo.…”
Section: Vardenafil and Tadalafil Have Advantages Over Sildenafil S Dmentioning
confidence: 91%
See 3 more Smart Citations
“…37 As with sildenafil, exercise testing in men with stable coronary artery disease, showed that vardenafil at 10 mg did not impair the ability of 41 patients to exercise at levels equivalent or greater than attained during sexual intercourse. 38 At baseline (1 h after taking vardenafil or placebo), systolic and diastolic blood pressure was 6 and 5 mm Hg less, respectively, with vardenafil than placebo, and heart rate was 3 beats/min higher. 38 At peak exercise, vardenafil did not alter blood pressure or heart rate, relative to placebo.…”
Section: Vardenafil and Tadalafil Have Advantages Over Sildenafil S Dmentioning
confidence: 91%
“…38 At baseline (1 h after taking vardenafil or placebo), systolic and diastolic blood pressure was 6 and 5 mm Hg less, respectively, with vardenafil than placebo, and heart rate was 3 beats/min higher. 38 At peak exercise, vardenafil did not alter blood pressure or heart rate, relative to placebo. 38 There are no peerreviewed published studies of the interaction between vardenafil and the nitrates.…”
Section: Vardenafil and Tadalafil Have Advantages Over Sildenafil S Dmentioning
confidence: 91%
See 2 more Smart Citations
“…None of the PDE5 inhibitors worsened ischemia or caused coronary vasoconstriction; [33][34][35][36][37] in some studies, there were actually improvements, in time, to ischemia and improved coronary vasodilator reserve. 33,35,37 Vardenafil slightly increases the QTc on the electrocardiogram and is not recommended in patients with congenital prolonged QT interval or in patients taking type 1A antiarrhythmic agents (such as quinidine or procainamide) or type three antiarrhythmics (such as sotalol or amiodarone). 23,38 As the PDE5 inhibitors are all mild vasodilators they may on their own cause small reductions in systolic and diastolic blood pressure, which, in general, are not considered clinically significant.…”
Section: Next Stepmentioning
confidence: 99%